Analisis Manajemen Kelembagaan untuk Penerapan Mekanisme Pembayaran Jasa Lingkungan Air Bersih di Hulu DAS Latuppa Kota Palopo - Yasir, Jibria Ratna; Syaukat, Yusman; Ekayani, Meti (Jurnal Aplikasi Manajemen, 2016)
The massive number deforestation and forest conversion in headwaters of Latuppa stream for providing agricultural lands and housings make the forests loss its functions as a prop of downstream and as a regulator of water cycle. It also prevents flood, landslide, andÂ dryness. Both activities significantly affect on clean water consumers and production ofÂ PDAM from which Latuppa stream is a primary source of water supply. Therefore, ForestryÂ Department supported by some stakeholders initiate a program concerning to the paymentÂ of environmental service for clean water as an alternative to solve the problem related toÂ exploitation of forest area in Latuppa. The purpose of this research is to identify individualsÂ who involve in organizational mechanism payment of environmental service and operationalmanagement in organization using stakeholders' analysis. The finding shows that theÂ primary organizer in environmental services mechanism is PDAM Palopo as a facilitator inÂ providing clean water supply supported by local people at headstream of Latuppa, especiallyÂ the group of To'Buangin and Se'pon, Wallacea Palopo, DAS Paremang forum, ForestryÂ Department of Palopo, Agriculture Department of Palopo, PSDH, BLH Palopo, andÂ BPDAS Saddang as a secondary stakeholder and organizer representatives who facilitatean initiative of payment to environmental service.